Intracytoplasmic Sperm Injection with Testicular Spermatozoa in Men with Azoospermia - Windt, M.-L. (Kluwer Academic Publishers-Plenum Publishers, 2002)
Purpose: The aim of the study was to gain an insight into the optimal management of the infertile couple with the husband suffering from azoospermia. Methods: One hundred and forty-two intracytoplasmic sperm injection (ICSI) cycles performed with testicular extracted spermatozoa were retrospectively analysed. The following factors were investigated for their possible influence on fertilization, cleavage, damage, pregnancy, and ongoing pregnancy rates; the use of fresh, cryopreserved, and preincubated (24 h) spermatozoa and the etiology of the husbands' azoospermia (obstructive and nonobstructive). All microinjections were performed with apparently normal spermatozoa—a head with a tail of normal length. In 116 cycles at least two embryos were available for transfer. Results: The overall fertilization, clinical pregnancy, and ongoing pregnancy rates obtained for the 116 cycles were 65.0, 30.2, and 22.4% respectively. Similar outcomes were obtained for cycles using fresh testicular and cryopreserved testicular spermatozoa. Similarly, no significant differences were obtained between the cycles using spermatozoa from obstructive or nonobstructive azoospermic patients. An increase in motility after a 24-h preincubation was observed, and although this group was relatively small (n = 17), a significant improvement in fertilization (73.7%) and pregnancy (53.9%) rate was obtained when the testicular sample was preincubated for 24 h. This improvement prevailed in the obstructive azoospermic group, but was less pronounced in nonobstructive patients. Conclusions: This study shows that the outcome of fresh and frozen–thawed testicular spermatozoa in ICSI is comparable, obstructive and nonobstructive etiologies perform the same, and that preincubation of testicular spermatozoa results in increased fertilization and pregnancy rates. All testicular biopsies are therefore performed the day before oocyte retrieval, superfluous spermatozoa cryopreserved, and the remaining testicular homogenate preincubated for the 24 h prior to oocyte retrieval. With this regime, most azoospermic patients are treated successfully, irrespective of the use of fresh or frozen–thawed spermatozoa from obstructive or nonobstructive cases.